Modernizing education system in Pondok Sungai Durian, Kuala Krai, Kelantan / Mohd Zahirwan Halim Zainal Abidin ... [et al.] - Zainal Abidin, Mohd Zahirwan Halim; Ismail, Huzaimah; Yusof@Salleh, Muhammad Yusri; Hassan, Paiz; Mohd Noh, Abd. Munir; Mohd Noor, Ahmad Firdaus (Universiti Teknologi MARA, Perlis, 2020)
Pondok is the earliest traditional Islamic education institution established in Malaysia in the 19th century. Kelantan is one of the states in Malaysia with many pondoks until it’s known as "Serambi Mekah" (the veranda of Mecca). However, the pondok system has experienced a drastic decline since the 20th century and some were closed. Among the factors that led to the fall of this institution are the challenges from modern educational institutions such as the schools and madrasah, the death of teachers and the dependence on the traditional system of studies. So, the pondok system needs to be modernised with the purpose to spread Islamic education and knowledge to the Muslim community in Malaysia today. Hence, the objective of this study is to review the development of Pondok Sungai Durian and to study the modernisation of the education system practiced by this pondok. To achieve this objective, this study used qualitative method of study, which were the library research and field studies based on document analysis, interviews and observations at Pondok Sungai Durian to obtain research data. The findings show that the transformation of Pondok Sungai Durian has created harmonisation between traditional learning system based on the halaqah, talaqqi and the use of turath kitab with the modern system based on a classroom system with a more contemporary syllabus. In addition, this system encourages and enhances students' knowledge as they are exposed to the traditional and modern studies at the same time, and this is important in generating the culture of knowledge and producing authoritative `ulama’ in this era of globalisation. Hence, the survival of Pondok Sungai Durian as a centre of Islamic education that retains the elements of traditional and modern studies is very relevant today. The development of the pondok system, especially Pondok Sungai Durian, has contributed to the development of charismatic characters among the `ulama’ (Islamic scholars), the intellectual development, da'wah and the growth of Islamic knowledge among Muslim community.